Hispanic migration and urban development studies from Washington DC - Pumar, Enrique S., 1956- (Research in race and ethnic relations ;, 2012)
This volume of Research in Race and Ethnic Relations analyzes the pattern of assimilation and incorporation among the Hispanic population in the Washington DC metro region. Following a comprehensive introduction looking at theoretical and policy implication the book consists of two conceptual chapters discussing the literature of ethnic incorporation and assimilation in urban regions, one chapter analyzing demographic trends among the Hispanic population, and four chapters analyzing different issues related to assimilation, in particular the nature entrepreneurialship, civic engagement, political participation, and education among migrants. This book makes a considerable contribution to the literature of emerging gateways in the field of migration and urban development with articles from notable academics and public policy analysts in their respective fields. It is the only comprehensive study of its kind concerning Hispanic migration to the Washington DC region. (The majority of other studies in the field are based on data from major metropolitan cities such as New York, Chicago and Los Angeles).